ЛЮМИНЕСЦЕНЦИЯ ПЛАГИОКЛАЗОВ ИЗ ГОРНЫХ ПОРОД НЕКОТОРЫХ ДРЕВНИХ СТРУКТУРНЫХ ЗОН ЕВРОПЕЙСКОГО КОНТИНЕНТА - Морошкин В.В. (My University, 2006)
Luminescence was studied for plagioclascs from various types of sialic rocks occurring within large consolidated structures of Precambrian basement - crystalline shields of East-European platform, and the so called «median massifs» (Zwischengcbirgc) in the folded areas of Central and West Europe. Some general regularities of the luminescence variations (degree of participating for different luminogens) reflect peculiarities of tecto-no-magmatic and gcochcmical evolution as of separate regional structures, so of the common geologic-tectonic history of continental crust for the whole European continent.
Keywords: 549:535.37; Палеозой::Кембрийская; Докембрий